Determination of contact stresses between mode I crack faces - Kaminsky, A. A.; Selivanov, M. F.; Chornoivan, Y. O. (Reports of the National Academy of Sciences of Ukraine, 2016)
A problem of determination of contact stresses in an isotropic body with a rectilinear mode I crack is stated and solved. The body is loaded by tensile stresses at inﬁnity and by concentrated compressive forces applied transversally to the crack line.